The use of brain CT Scan in craniocerebral trauma with Glasgow coma scale scores of 13 â 15 in Dr. Cipto Mangunkusumo Hospital 1999-2001 (Faculty of Medicine Universitas Indonesia, 2004)
There is still a controversy among the neurologists whether brain CT scan must be performed on the mild head trauma patients. This study was executed to find out the correlation between the brain CT scan image findings and its clinical impairment among the mild head trauma patients with Glasgow coma scale (GCS) score of 13 to 15. The study was a retrospective study by analyzing the uniform medical records of the head trauma patients hospitalized at the Neurology ward of Dr. Cipto Mangunkusumo Hospital within the period of 1999 to 2001. During that period 1,663 patients were hospitalized due to head trauma, and 1,166 of them (70.1 %) were suffered from mild head trauma patients with GCS score of 13-15. Among those with brain CT scan examinations (N: 271), the neurological abnormalities were found on 144 (53.1%) of patients, consisted of cerebral edema (11,4%), intracerebral hemorrhage (5.5%), epidural hemorrhage (16.2%), subdural hemorrhage (18.1%), subarachnoid hemorrhage (5.5%), and combination (13.8%). The further analysis showed that cranial nerves disturbance, amnesia, loss of conciousness for more than 10 minutes, and vomiting are significantly correlated to the brain CT scan abnormality. Combination of the above four clinical signs and symptoms have sensitivity of 90 % in predicting brain insults. This findings may be used as a simple set of clinical criteria for identifying mild head trauma patients who need undergo CT scan examination. (Med J Indones 2004; 13: 156-60) Keywords: mild head injury, brain CT scan